PENERAPAN FULL DAY SCHOOL DI SD MUHAMMADIYAH 1 PANJI SITUBONDO TAHUN 2017 - Reky Lidyawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
The blowing of information on the implementation of the full day school program at both elementary and secondary schools has brought tremendous dynamism among educators, whether formal or non-formal school educators. There is tremendous concern to madrasah educators who feel they will be threatened when a full day school program is held, as schoolchildren start in the morning and come home late in the afternoon so there is no chance for children to study religious studies in madrasah. This anxiety produces a rejection of the policy that will be launched by the minister of education. The purpose of this research is to know the implementation of full day school in SD Muhammadiyah 1 Panji. The location of this research was conducted at SD Muhammadiyah 1 Panji Kabupaten Situbondo district consisting of grade 4 class 5 and sixth grade with details of class 4 sofa and marwah each 25 students, class 5 sofa and marwah each 32 students and class 6 sofa and marwah each 25 students. This research is a qualitative research. Qualitative research is a research that produces descriptive data in the form of data written or oral from the people and behavior that can be observed .. Data collected is the data implementation of full day school in SD Muhammadiyah 1 Panji. Based on the analysis of research data, the implementation of full day school in SD Muhammadiyah 1 Panji is applied to high class only in classes 4, 5 and 6. Full day school implementation in classes 4 and 5 last at 15.30 pm and grade 6 to 17.00 pm